A first principles study on electrochemical sensing of highly toxic pesticides by using porous C4N nanoflake. (January 2022) - Asif, Misbah; Sajid, Hasnain; Ayub, Khurshid; Ans, Muhammad; Mahmood, Tariq
Abstract: C4 N is a novel porous two-dimensional material with fascinating electronic and chemical properties. Thereby, the sensing ability of C4 N is the most aspect topic of research nowadays. In this study, potential application of C4 N nanoflake as a chemical sensor for the toxic pesticides has been investigated using density functional theory calculations. The sensing ability of C4 N for pesticides is evaluated through the interaction energy, noncovalent interaction index (NCI), quantum theory of atoms in molecule (QTAIM), molecular orbitals and CHELPG charge transfer analyses. The first principle calculations on ωB97XD/6-31G(d, p) level of DFT show that the C4 N is selectively sensitive to Dichlorodiphenyltrichloroethane (DDT), Fenitrothion (FNT), Dimethoxy (DMDT), Ronnel (RN) and Fenthion (FT). The interaction of pesticides leads to the significant changes in the electronic structure of C4 N. The observed sequence of interaction energy of our reported complexes is DDT@C4 N > FNT@C4 N > DMDT@C4 N > RN@C4 N > FT@C4 N. The electronic structure changes can be demonstrated from two aspects: the strong interaction between pesticide molecule and C4 N, the variation in HOMO-LUMO orbital energies and charge transfer from C4 N to pesticide. The charges distribution between analytes and C4 N nanoflake on interaction is analyzed by the electron density differences (EDD) and charge decomposition analysis (CDA). Our results reveal the potential application of C4 N in electronic and sensor devices especially for the detection of toxic chemicals. Graphical abstract: Image 1 Highlights: The sensing of C4 N nanoflake toward pesticides is investigated theoretically. The results are based on the geometric, energetic, and electronic analyses. ωB97XD and M052X-D3/6-31G (d, p) levels of DFT are implemented to measure the sensing affinity of C4 N. The thermodynamic stability is in the order of DDT@C4 N > FNT@C4 N > DMDT@C4 N > RN@C4 N > FT@C4 N.